Implementasi Kebijakan Penerimaan Peserta Didik Baru (PPDB) Melalui Sistem Zonasi Untuk Pemerataan Kualitas Pendidikan - Indri Novrijayanti; Yulia Wiji Astika (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2020)
AbstractThe purpose of this study was to find out how the implementation of the New Student Admissions (PPDB) policy through the zoning system for equal distribution of education quality at SMP Negeri 9 Muara Bungo, to find out the obstacles and efforts made in implementing the New Student Admissions (PPDB) policy through the system zoning for equal distribution of education quality at SMP Negeri 9 Muara Bungo. The method used in this study was descriptive method with a qualitative approach with a population, namely the head and vice principal of the school, teachers and staff of SMP Negeri 9 Muara Bungo, the chairman of the committee and members of the guardians of students, and students of SMP Negeri 9 Muara Bungo. The sample taken in this study amounted to 13 (thirteen) people with purposive sampling technique to determine the subject / object according to the purpose. The results showed that the implementation of the New Student Admissions (PPDB) policy through the zoning system for equal distribution of education quality at SMP Negeri 9 Muara Bungo has been implemented in accordance with PERMENDIKBUD Number 14 of 2018 and PERBUP Bungo Number 35 of 2018, in terms of obstacles seen from 4 variables. According to Smith, there were 3 variables that are still experiencing obstacles, namely the target group, the implementing agency, and environmental factors. Efforts are being made, namely submitting reports to the Bungo Education Office, improving Human Resources (HR) and computer facilities, and improving school performance